Semi-Open Sets and Semi-Closure of a Set - Canoy, Sergio Jr.; Lemence, Richard (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper revisits the concept of semi-open set in a topological space defined by N. Lcvi11c in 1963 [2). We ah;o define new concepts such as semi-closed set, and semi-closure point of a set and give some results concerning these concepts.